2016
DOI: 10.1007/s00508-016-1059-9
|View full text |Cite
|
Sign up to set email alerts
|

Displaced juvenile Tillaux fractures

Abstract: SummaryBackgroundApproximately 15 % of all juvenile injuries of the long bones involve the epiphyseal growth plate, and 2.9 % of these are juvenile Tillaux fractures. The Tillaux fracture is of great importance because it involves a major weight-bearing articular surface. Treatment protocols in the literature are not uniform for this kind of fracture, and numerous case reports can be found describing various treatment methods. The aim of this study was to present the clinical outcome at long-term follow-up aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Studies suggesting open reduction and internal fixation advocate immobilization for at least four weeks postoperatively. [3,18] The current study's results were similar, with two weeks of immobilization applied during patient follow-up based upon the patient's age concerning rehabilitation and the status of the fracture. In addition, we wanted to prevent Achilles tendon and joint contracture during the follow-up of immobilized intra-articular fractures, prevent reflex sympathetic dystrophy, and facilitate rehabilitation, [15,24] In our opinion, early removal of the splint and the start of rehabilitation do not alter functional results in the long term, but it facilitates rehabilitation in the short term and may allow them to return to daily activities more easily.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Studies suggesting open reduction and internal fixation advocate immobilization for at least four weeks postoperatively. [3,18] The current study's results were similar, with two weeks of immobilization applied during patient follow-up based upon the patient's age concerning rehabilitation and the status of the fracture. In addition, we wanted to prevent Achilles tendon and joint contracture during the follow-up of immobilized intra-articular fractures, prevent reflex sympathetic dystrophy, and facilitate rehabilitation, [15,24] In our opinion, early removal of the splint and the start of rehabilitation do not alter functional results in the long term, but it facilitates rehabilitation in the short term and may allow them to return to daily activities more easily.…”
Section: Discussionsupporting
confidence: 58%
“…Tiefenboeck et al [3] reported 90% excellent results in their study, which included seven patients undergoing open surgical internal fixation. They reported limitation of motion in the ankle as a complication in one patient.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Cho et al 5 suggested coracoclavicular stabilization techniques or transacromial intramedullary fixation for this type of fractures, whereas others have suggested traditional hardware (locking plates) but with additional coracoclavicular augmentation. 9,35,36 The limitations of our systematic review lie with those of the included studies. All included studies were retrospective cohort, or case series, with a moderate to high risk of bias, deeming the level of evidence of our review as low.…”
Section: Discussionmentioning
confidence: 99%